The Analysis of The Relation of Information System to Organizational Learning in Increasing Financial Performance in 3, 4 And 5-Star Hotels In East Java - Andrew William Sanjaya; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of information system to organizational learning; organizational learning to financial performance; and information system to financial performance in the 3, 4 dan 5-star hotels in East Java. This study also examined the indirect and significant relationship of information system to financial performance through organizational learning as intervening variable in the 3, 4 dan 5-star hotels in East Java.The data were obtained by distributing questionnaires to 3, 4 dan 5-star hotels in East Java. This study used a quantitative approach, and processed by using smart PLS software. The respondents in this research were accounting, finance, marketing staf, supervisor, manager and chief executive in the 3, 4 dan 5-star hotels in East Java. This study showed that there was a positive and significant relationship of information system to organizational learning, organizational learning to financial performance, and information system to financial performance in the 3, 4 dan 5-star hotels in East Java. But, organizational learning was inadequate as an intervening variable between information system and financial performance because organizational leaning gave a smaller affect than the direct effect. It meant that organizational learning could not be a mediator between information system and financial performance.